Analisis Studi Literatur Pengembangan Media Berbasis Algoritma Pemrograman Dalam Pembelajaran Matematika - Azra Sabrina; Yahfizham Yahfizham (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
A multitude of software and media have been made possible by technological advancements, which may be utilized to produce more engaging and successful mathematics learning experiences. By using algorithms and programming languages, the software can run well. Reviewing educational materials that may be utilized to advance mathematical learning, together with their impacts and difficulties, is the goal of this study. This piece employs the technique of Systematic Literature Review (SLR). This SLR research aims to find, study, and evaluate comparable research to answer research questions. The development of mathematical learning through the use of learning materials based on algorithms according to previous research most people use geogebra and matlab. This study solely addresses the application of algorithm-based media programming in the advancement of mathematical learning, in accordance with earlier publications. It is anticipated that future academics will be able to advance mathematics learning using the algorithm-based media of this programming.